Atlantic‐Pacific seesaw and its role in outgassing CO2 during Heinrich events. (30th January 2014) - Menviel, L.; England, M. H.; Meissner, K. J.; Mouchet, A.; Yu, J.
<x xml:space="preserve">Abstract</x> [1] Paleoproxy records indicate that a marked weakening of the Atlantic Meridional Overturning Circulation (AMOC) during Heinrich events was often accompanied by a notable atmospheric CO2 increase. However, previous modeling studies display conflicting atmospheric CO2 responses to an AMOC shutdown. Here we use model simulations combined with paleoproxy records to show that depending on the deep and bottom water transport in the Northern and Southern Pacific Ocean during an AMOC weakening, the ocean can act either as a sink or a source of carbon. Results from idealized meltwater experiments as well as from a transient experiment covering Heinrich stadial 4 suggest that a shutdown of the AMOC during Heinrich stadials 4 (HS4) and 1 (HS1) led to an enhancement of Antarctic Bottom Water (AABW) and North Pacific Deep Water (NPDW) transport. We show that enhanced deep and bottom water transport in the Pacific Ocean ventilates deep Pacific carbon through the Southern Ocean, thus contributing to a rise in atmospheric CO2. This mechanism yields a good agreement between paleoproxy records and modeling results, thus highlighting the possible establishment of an Atlantic‐Pacific seesaw during Heinrich stadials. Enhanced AABW and NPDW transport could account for most of the observed atmospheric CO2 increase during HS4 and for about 30% of the atmospheric CO2 increase during HS1.